Study on coupling between mineral resources exploitation and the mining ecological environment in Shanxi Province - Wu, Wenjing; Zhou, Jinsheng; Niu, Jianying; Lv, Haodong (Environment, development and sustainability, 2021)
Due to rapid socioeconomic development, seeking the coordination of resources exploitation and the ecological environment has become an objective requirement for the healthy and sustainable development of the mining industry. This paper selects 23 indicators with which to construct an evaluation index system for mineral resources exploitation and the mining geological ecological environment of Shanxi Province from 2003 to 2015. It then establishes a development index model, a coupling degree model and a coupling coordination degree model. Using a time-series analysis, the comprehensive development level, coupling status and coupling coordination degree of the two systems are analyzed. The results are threefold. (1) The overall level of mineral resources exploitation improved, but, after 2012, the level dropped significantly. The ecological environment in the mining area has improved as a whole, but, due to the ecological fragility caused by long-term extensive mining and acute treatment, the state of the ecological environment fluctuates greatly. (2) The coupling degree between mineral resources exploitation and the mining ecological environment is stable, and it has been in the antagonistic stage for a long time. Although the degree of coupling coordination has improved, it remains at a low level. (3) Further improvement in the coordination between mining exploitation and the mining ecological environment in Shanxi Province has been restricted due to several indicators with greater weights. Recommendations to be considered by policy makers include insufficient sustainable development concepts, outstanding historical issues and the lack of guarantees for environmental protection funds.